A Diterpene as an Endogenous Signal for the Activation of Defense Responses to Infection with Tobacco mosaic virus and Wounding in Tobacco - Seo, Shigemi (American Society of Plant Biologists, 2003)
In pathogen-infected or wounded tobacco plants, the activation of wound-induced protein kinase (WIPK), a tobacco mitogen-activated protein kinase, has been implicated in the defense response. However, no endogenous signal responsible for the activation has been identified. A WIPK-activating substance was isolated from tobacco leaves and identified as (11E,13E)-labda-11,13-diene-8α,15-diol, designated WAF-1. When applied in nanomolar concentrations to leaves, either natural WAF-1 or chemically synthesized WAF-1 activated WIPK as well as salicylic acid–induced protein kinase, a tobacco mitogen-activated protein kinase, and enhanced the accumulation of transcripts of wound- and pathogen-inducible defense-related genes. Quantitative analysis of endogenous WAF-1 revealed that levels increased rapidly in leaves during a hypersensitive response to Tobacco mosaic virus (TMV) and after wounding. Furthermore, treatment of leaves with WAF-1 resulted in enhanced resistance to TMV infection. These results suggest that WAF-1 functions as an endogenous signal to mediate the defense responses of tobacco plants to TMV infection and wounding.